A macropolítica da assistência farmacêutica e a programação de ações e serviços do Sistema Único de Saúde (SUS) - Santos, Diana Graziele dos (2015)
From the macro-politics of Pharmaceutical Services, can be seen major advances in the construction of Brazilian Health System (SUS). Despite, the challenge to the federal management of health is the building of policies that ensure the inclusion of shares and pharmaceutical services in the general context of health in the SUS by changing the hegemonic standard of management and production practices of health from the perspective of building a network of more integral services. The changes in this context require an understanding of the pharmaceutical services in the space of brasilian health reform and your relationship with the planning and programing of the health. This work is located in the field of federal management of health and aims to study, within the space of macro-politics, the construction process from pharmaceutical services incorporated into the framework of the General Programming of Actions and Health Services (PGASS), through the theoretical references of the Foucault and also historical and dialectical materialism, which the analysis categories: the pharmaceutical services in Health Care Networks ( RAS ); the consolidation of pharmacies like health facilities; and the pharmaceutical services integrated to the general programming of the health. This study focused a literature review and the experience of the researcher in the federal health management, bringing to light a theoretical reflection on the experienced practices, Institutional documents and texts produced.